Misdaad en die impak daarvan op die mens – ’n Christelike perspektief - Steyn, M. M. (Koers, 2004)
Crime and its impact on man – a Christian perspective Crime is a depressing and frightening reality, especially within the South African context. In this article the following aspects are discussed from the vantage point of a Christian world view: the concept crime, its impact on ‘victims’, and the care-taking of victims’ needs. Crime has a two-sided effect: it affects the victim and the perpetrator as well as their next of kin. Problematic issues regarding crime are outlined in the introductory part of the article. Subsequently a Christian perspective and what this frame of reference implies are discussed. On the basis of this perspective it is argued that crime is in essence a transgression of universal laws as well as of laws applied by governments and other authorities. When one lives lawlessly one implicitly and explicitly does not obey God’s commandment to love one’s neighbour and to honour and glorify God. As a result of the emotional ‘distance’ between a person affected by crime and a perpetrator, a crime-affected person is often not able to react and behave as can be expected of a believer whose way of life is intended to honour God. In addition to possible negative behavioural patterns and reactions, post-traumatic stress can contribute to dysfunctional development of traumatised people’s potential. The Word of God teaches that care should be given to the interests of one’s neighbour (in this case ‘neighbour’ implies both perpetrator and crime-affected person). A person affected by crime deserves the attention and support of both care-giving professionals and of members of the community at large.